While the Climate Always has and Always Will Change, there is No Climate Crisis - Manheimer , Wallace (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 9, 2023)
The emphasis on a false climate crisis is becoming a tragedy for modern civilization, which depends on relible, economic, and environmentally viable energy. The windmills, solar panels and backup batteries have none if these qualities. This falsehood is pushed by a powerful lobby which Bjorn Lomborg has called a climate industrial complex, comprising some scientists, most media, industrialists, and legislators. It has somehow managed to convince many that CO2 in the atmosphere, a gas necessary for life on earth, one which we exhale with every breath, is an environmental poison. Multiple scientific theories and measurements show that there is no climate crisis. Radiation forcing calculations by both skeptics and believers show that the carbon dioxide radiation forcing is about 0.3% of the incident radiation, far less than other effects on climate. Over the period of human civilization, the temperature has oscillated between quite a few warm and cold periods, with many of the warm periods being warmer than today. During geological times, it and the carbon dioxide level have been all over the place with no correlation between them.